2005
DOI: 10.1016/j.ydbio.2004.12.011
|View full text |Cite
|
Sign up to set email alerts
|

VEGF directs newly gastrulated mesoderm to the endothelial lineage

Abstract: Herein, we investigated the role of VEGF signaling in the earliest events in vasculogenesis and found that it exerts critical effects shortly after mesodermal cells form by gastrulation. We showed that VEGF treatment of embryos caused an increase in the population of newly gastrulated mesodermal (NGM) cells that express the transcription factor TAL1. This increase in TAL1-positive cells was attributed to VEGF induction of VEGF receptor-2 (Flk1)-positive NGM cells that would normally not have been induced due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Interestingly in the chick embryo, Indian Hedgehog is regionalized and expressed exclusively in the yolk sac endoblast, the mouse equivalent of the visceral endoderm (TJ personal communication); furthermore, the dynamic expression of Gata2 during the onset of yolk sac erythropoiesis, showed that this factor is expressed very early during gastrulation in groups of cells, likely to represent the first endothelial precursors, in close association with the endoderm [3]. These first endothelial precursors are formed under the control of a VEGF-VEGF-R2 axis that triggers expression the SCL-Tal1 transcription factor and the subsequent commitment into the endothelial lineage [30]. In addition to endothelial precursors, SCL-Tal1 was shown to be regulated by a transcription factor complex that consists of Fli-1, Elf-1, two ETS-related transcription factors and Gata-2 [31].…”
Section: The Crucial Role Of the Endodermmentioning
confidence: 99%
“…Interestingly in the chick embryo, Indian Hedgehog is regionalized and expressed exclusively in the yolk sac endoblast, the mouse equivalent of the visceral endoderm (TJ personal communication); furthermore, the dynamic expression of Gata2 during the onset of yolk sac erythropoiesis, showed that this factor is expressed very early during gastrulation in groups of cells, likely to represent the first endothelial precursors, in close association with the endoderm [3]. These first endothelial precursors are formed under the control of a VEGF-VEGF-R2 axis that triggers expression the SCL-Tal1 transcription factor and the subsequent commitment into the endothelial lineage [30]. In addition to endothelial precursors, SCL-Tal1 was shown to be regulated by a transcription factor complex that consists of Fli-1, Elf-1, two ETS-related transcription factors and Gata-2 [31].…”
Section: The Crucial Role Of the Endodermmentioning
confidence: 99%
“…Based on studies indicating a relationship between EC numbers and vascular patterning, [8][9][10] we next evaluated the effects of varying the ratio of endothelial to fibroblast cells within high-density cocultures. Analysis of 1:4 EC to fibroblast rod constructs cultured for 3 days and then immunolabeled with antibodies to CD31 showed the formation of in vivo-like primary vascular networks extending throughout the entirety of the tissue construct and exhibiting directional alignment (Fig.…”
Section: In Vitro Generation Of Vascularized Tissue Constructsmentioning
confidence: 99%
“…8,9,12,16 Differential network patterning resulting from different ratios of cell types was also supported by previous studies investigating the relationship between the EC mitogen VEGF and embryonic vasculogenesis. [10][11][12]17 While observing that CD31 + networks spanned the entirety of the 1:4 EC:fibroblast-derived tissues, it was surprising to notice distinct directional organization specific to regions within the tissues. Specifically for rod constructs, networks organized perpendicular to the direction of lateral condensation within the central region of the construct and parallel to the tissue-media border at the periphery of the construct (Fig.…”
Section: Primary Vascular Network Formation Requires Specific Ratio Omentioning
confidence: 99%
“…Thus, these observations have suggested but have not proved the existence of hemangioblasts. In chick, the VEGF-VEGFR2 signaling is essential for generating TAL1 ϩ angioblasts that can give rise to QH1 ϩ endothelial cells but their fates to hematopoietic lineages were not extensively examined (QH1 is a monoclonal antibody that recognizes quail endothelial and hematopoietic cells; Giles et al, 2005). Therefore, it remains unclear if VEGFR2 ϩ and/or TAL1 ϩ cells have hemangioblastic potential, giving rise to primitive hematopoietic and endothelial progenitors in the chicken gastrula.…”
Section: The Hemangioblast Hypothesis Was Proposed and Supported Frommentioning
confidence: 99%